PEMBERDAYAAN PENGAJAR DALAM MENINGKATKAN MOTIVASI KESEHATAN MENTAL DAN GIZI SEIMBANG PADA SANTRI DI PONDOK PESANTREN AL AMALUL KHAIR - Aghadiati, Faradina; Fadillah Heryanda, Mahfuzhoh; Ardila, Devi (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Adolescent students in Islamic boarding schools are vulnerable to nutritional and mental health problems due to unbalanced diets, academic pressure, and limited health services. This community service aimed to enhance teachers’ and food handlers’ understanding of balanced nutrition and mental health at Al Amalul Khair Islamic Boarding School, Palembang. The program employed interactive lectures, healthy product demonstrations, and basic counseling training. Evaluation was conducted through pre- and post-tests to measure knowledge improvement and direct observation of skills. Results indicated a significant increase in teachers’ knowledge (from 58.3% to 84.7%, p<0.05), improved skills in preparing nutritious products, and the establishment of a Health Team and teacher counselors. In conclusion, integrating nutrition education, healthy food innovation, and psychosocial support effectively strengthened teachers’ capacity and provided a replicable model for other schools.